COVID-19 Impact Monitoring at the Household Level : Burkina Faso, Brief No. 4 - Tsimpo Nkengne, Clarence; Tiberti, Marco; Backiny-Yetna, Prospere R.; Constantinidis, Stavros; Koncobo, Zakaria; Tiendrebeogo, Adama (World Bank, Washington, DC, 2021)
This note presents the results of the fourth round of a nationally representative telephone survey (HFPS). Data collection took place between November 06 and December 02, 2020. In addition to the 2,013 households successfully interviewed in the third round, in an effort to maintain sample size, additional 91 households that had not been successfully interviewed in previous rounds but did not refuse to participate in the survey were called in this fourth round and 2,011 (95.58 percent of the sample) were successfully interviewed in Round 4. The questionnaire includes key modules that were administered in previous rounds, namely, access to food and health services, employment and income, and shocks. A new module on credit is added.